Battles of the crusades 1097-1444 from Dorylaeum to Varna - Devries, Kelly; Dickie, Iain; Dougherty, Martin J.; Jestice, Phyllis G.; Jorgensen, Christer; Pavkovic, Michael F. (Amber Books, 2019)
When Pope Urban II called European Christianity to stem the expansion of Islamic states into Europe, he set off a train of events that would last many hundreds of years and have far reaching political and economic consequences. Battles of the Crusades introduces 20 key battles from this period of religiously inspired conflict in Europe and the Middle East. Beginning with the battle of Dorylaeum (1097) and finishing with the battle of Varna (1444), examples from every era and campaign are featured. Apart from such well-known encounters as Antioch, Jerusalem and Harran, battles between the Crusader states and their Muslim neighbours include Montgisard and Saladin's destruction of the Crusader army at Hattin. Beyond the Middle East, featured battles include the Christian recapture of Lisbon and the massacre of the Albigensians at Beziers in France. Battles from the Reconquista of Spain and the expansion of the Teutonic Knights make this a rounded account of 500 years of religious conflict. Each entry includes a contextual introduction, a concise description of the action, and an analysis of the aftermath. A specially commissioned colour map illustrating movement of forces brings the subject to life and helps the reader to grasp the development of the battle. With more than 200 colour and black-and-white maps, artworks, and photographs, Battles of the Crusades provides an accessible introduction to key engagements of the Medieval era.